(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Global trade has undergone significant transformations in recent decades, with China’s accession to the World Trade Organization (WTO) in 2001 marking a pivotal moment. The integration of the world’s most populous country into the global trading system has had profound implications for the distribution of goods and services worldwide. China’s rapid economic growth and industrialization have reshaped the dynamics of international trade, shifting production patterns and supply chains. As China has become a major player in the global economy, its policies and practices are scrutinized for their impact on trade flows, market competition, and global economic stability. Understanding the impact of China’s WTO accession on global trade is crucial for policymakers, businesses, and economists alike as they navigate the complexities of a rapidly evolving international trade landscape. By examining the nuances of China’s participation in the WTO, we can gain insight into the broader implications for the global economy